Embodying culture : pregnancy in Japan and Israel - Ivry, Tsipy (Studies in medical anthropology., 2010)
Embodying Culture is an ethnographically grounded exploration of pregnancy in two different culturesùJapan and Israelùboth of which medicalize pregnancy. Tsipy Ivryfocuses on "low-risk" or "normal" pregnancies, using cultural comparison to explorethe complex relations among ethnic ideas about procreation, local reproductive politics, medical models of pregnancy care, and local modes of maternal agency.